A Qualitative Study on How Younger Women Experience Living with an Ostomy - Mørkhagen, Andrea Emilie; Nortvedt, Line (International Journal of Environmental Research and Public Health, 2023)
There is a growing demand that ostomy patients receive more systematic and individualised follow-up by ostomy nurses. The purpose of the study was to explore how younger women experience everyday life after an ostomy and to map what healthcare personnel can do to ensure that the patient group can feel safe and looked after. This qualitative study included four younger women who had a stoma fitted. Individual in-depth interviews were conducted, and two participants were interviewed twice. The findings resulted in three main themes: (1) The importance of follow-up and information from healthcare personnel, (2) Experience with illness and freedom in everyday life and (3) Self-image and social relationships. We found that time to prepare before surgery and learning to live with the stoma provide a good basis for handling the new everyday life with a stoma. We conclude that ostomy nurses provide support and security to those undergoing ostomy operations. Healthcare professionals should focus on providing individually tailored information to ensure that patients are receptive to the information being shared with them. Having parts of a bowel removed can be experienced as relief, especially when the disease has previously contributed to poor self-image and social isolation.